Building Tourism from the Optimization of the Landscape as a Creative Economic Activity of the Community - ANWAR, Rully Khairul; HADIAN, Mohammad Sapari Dwi; HENDARMAWAN, HENDARMAWAN; KHADIJAH, Ute Lies Siti (Journal of Environmental Management and Tourism; Vol 11 No 4 (2020): JEMT Volume XI Issue 4(44) Summer 2020, 2020)
This study finds out how the processes of optimization of the landscape in Ciawi of Tasikmalaya of West Java of Indonesia raise the economic activities of the community. Having optimized, there were a series of economic activities, creative skills, attitudes, and responsibilities of the community to the preservation of the landscape. This study is qualitative in method and a case study in approach. Through such data collection techniques as observation, interviews, and documentary studies, this writing follows Miles and Huberman's interactive model in analysing the data. The results of this study show that the optimization of the landscape made by the residents of the volcanic eruption is useful in bringing the society back in the business by metamorphosing the environment to the new one. However, the condition brought about the growing attitudes of individualism in the community, leaving for the tradition of working together for society.